2013
DOI: 10.1111/jpc.12305
|View full text |Cite
|
Sign up to set email alerts
|

Three years of paediatric morbidity and mortality at the national hospital in Dili, East Timor

Abstract: The study provides, for the first time, an understanding of the admissions and outcomes of the busiest paediatric inpatient unit in East Timor. It emphasises important health system issues which impact on both data quality and hospital outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
5
11
2
Order By: Relevance
“…59.6% of admissions in our study is predominated by male neonates, which is similar to studies from Shivamogga and Pakistan that had 58% and 63% respectively [11,10]. Our study had 89.8% newborn admissions within 7 days of birth similar to Prasad v study which had 85.5% admissions within 10days of birth, where as a study from Timor, Africa had only 27% of admission within 7 days of life [9,12]. In this study 25% of admission was by preterms and 40.6% by low birth weight babies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…59.6% of admissions in our study is predominated by male neonates, which is similar to studies from Shivamogga and Pakistan that had 58% and 63% respectively [11,10]. Our study had 89.8% newborn admissions within 7 days of birth similar to Prasad v study which had 85.5% admissions within 10days of birth, where as a study from Timor, Africa had only 27% of admission within 7 days of life [9,12]. In this study 25% of admission was by preterms and 40.6% by low birth weight babies.…”
Section: Discussionsupporting
confidence: 87%
“…Sepsis was low 6.4% and 5.1% in studies from Bangladesh and Shivamogga [4,11].A study from Bihar (23.3%) had sepsis rates similar to the present study [14].Birth asphyxia (23.5%) was high in our study; however a study from Bangladesh had 28.5% [4]. Other studies showed the same to be lower than our study12%, 18.5% and 7.1% [12,14,11].High incidence in our study is because of referral of many high risk pregnancies with fetal distress to our centre for delivery as evidenced by 22% of babies born with MSAF. In this study Respiratory problem (HMD, MAS, TTN and BP) was 13.9%, while a study from Africa (22%) had higher than ours [12].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Timor‐Leste Demographic and Health Survey (TLDHS), a nationwide survey of selected households indicated a perinatal mortality rate (PNMR) of 20/1000 live births, a stillbirth rate of 3/1000 births and an early neonatal death rate of approximately 17/1000 live births . Published data from retrospective reviews at Hospital Nacional Guido Valadares (HNGV) indicated a stillbirth rate of 29/1000 births and a neonatal mortality rate (NNMR) of 18/1000 live births, without a specific assessment of early neonatal deaths . In comparison, Timor‐Leste's closest neighbours, Indonesia and Australia have stillbirth rates of 13/1000 and 7/1000 births and NNMRs of 14/1000 and 2/1000 live births, respectively…”
Section: Introductionmentioning
confidence: 99%
“…5 Published data from retrospective reviews at Hospital Nacional Guido Valadares (HNGV) indicated a stillbirth rate of 29/1000 births 6 and a neonatal mortality rate (NNMR) of 18/1000 live births, without a specific assessment of early neonatal deaths. 7 In comparison, Timor-Leste's closest neighbours, Indonesia and Australia have stillbirth rates of 13/1000 and 7/1000 births and NNMRs of 14/1000 and 2/1000 live births, respectively. 8,9 Accurate classification of causes and associated conditions for perinatal deaths may inform strategies to reduce mortality rates.…”
Section: Introductionmentioning
confidence: 99%